Brain-derived neurotrophic factor (BDNF) serum level in women with first-episode depression, correlation with clinical and metabolic parameters. (3rd April 2018) - Skibinska, Maria; Kapelski, Pawel; Rajewska-Rager, Aleksandra; Pawlak, Joanna; Szczepankiewicz, Aleksandra; Narozna, Beata; Twarowska-Hauser, Joanna; Dmitrzak-Weglarz, Monika
Abstract: Background: Brain-derived neurotrophic factor (BDNF) influences neuron differentiation during development, as well as the synaptic plasticity and neuron survival in adulthood. BDNF has been implicated in the pathogenesis of psychiatric disorders and its serum level is a potential biomarker for depression. The aim of this study was to examine serum levels of BDNF in first-episode depression and its correlation with clinical and metabolic parameters. Materials and methods: The study was performed on a group of 60 women: 30 diagnosed with a first-episode of depression and 30 healthy controls. 17-Item Hamilton Depression Rating Scale (HDRS-17) was used to assess the severity of depression. Patients were randomly chosen for treatment with sertraline or venlafaxine. BDNF serum levels and metabolic parameters: fasting serum glucose, cholesterol, triglyceride (TG), high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C) were measured at baseline and week 8 of treatment. Results: There were no differences between BDNF level in depressed patients compared with the healthy controls. Lack of differences in medication effect of sertraline or venlafaxine on HDRS-17 scores during 8 weeks of treatment was observed. Correlation of BDNF at baseline and fasting serum glucose at baseline and week 8 was detected. Conclusions: Correlations of BDNF serum levels with metabolic parameters were observed.